In Putin's footsteps : searching for the soul of an empire across Russia's eleven time zones - Khrushcheva, Nina L., 1964-; Tayler, Jeffrey (St. Martin's Press, 2019)
Two senior reporters on Russia and the former Soviet Union, including Nikita Khrushchev's great-granddaughter, combine travelogue, current affairs, and history in a chronicle demonstrating how Russia's dimensions have shaped its identity and culture.